Antiretroviral treatment leading to secondary trimethylaminuria: Genetic associations and successful management with riboflavin. (28th November 2020) - Scimone, Concetta; Alibrandi, Simona; Donato, Luigi; Giofrè, Salvatore V.; Rao, Giacomo; Sidoti, Antonina; D'Angelo, Rosalia
Abstract: What is known and objective: Trimethylaminuria is a metabolic disorder characterized by excessive excretion of trimethylamine in body fluids following FMO3 gene mutations. Secondary forms of the disease may be due to consumption of trimethylamine precursor‐rich foods or metabolism of some xenobiotics. Case summary: A HIV patient developed secondary trimethylaminuria following antiretroviral treatment. Riboflavin supplementation ameliorated his phenotype. 1 H‐NMR confirmed increased urine level of TMA. Several genes involved in choline catabolism harboured missense mutations. Riboflavin supplement improved enzymatic activity of mutated enzymes promoting TMA clearance. What is new and conclusion: Antiretrovirals may increase the concentration of TMA precursors. The present study reports antiretroviral treatment as risk factor for such secondary trimethylaminuria. Riboflavin is an effective treatment. Abstract : Secondary TMAU may arise due to high trimethylamine precursor intake by food or xenobiotics. Antiretroviral treatment can contribute to TMAU phenotype when specific genetic variants are harboured. Riboflavin supplement improved enzymatic activity of mutated enzymes ameliorating TMAU phenotype.